A word-frequency-preserving steganographic method based on synonym substitution. (2nd May 2019) - Xiang, Lingyun; Yang, Xiao; Zhang, Jiahe; Wang, Weizheng
Text steganography is a widely used technique to protect communication privacy yet it suffers from a variety challenges. One of these challenge is synonym substitution-based method, which may change the statistical characteristics of the content. For example, the word frequency may be changed, which may be easily detected by steganalysis. In order to overcome this disadvantage, this paper proposes a synonym substitution-based steganographic method taking the word frequency into account. This method dynamically divides the synonyms appearing in the text into groups, and substitutes some synonyms to alter the positions of the relative low frequency synonyms in each group to encode the secret information. By maintaining the number of relative low frequency synonyms across the substitutions, it preserves some characteristics of the synonyms with various frequencies in the stego and the original cover texts. The experimental results illustrate that the proposed method can effectively resist the attack from the detection using relative frequency analysis of synonyms.